A Method to Evaluate the Ultrastructure of Free Cells by Scanning Electron Microscopy - Alzamora-Gonzales, Libertad; Amat-Herbozo, Carolina de; Colona-Vallejos, Erasmo (International Journal of Membrane Science and Technology, 2023)
The aim of this study was to develop an easy method for the analysis of the surface ultrastructure in prokaryotic and eukaryotic free cells. The procedure to prepare three types of free cells, the adhesion to poly-L-lysin (PLL)-coated glass substrate, fixation, washing, dehydration in increasing ethanol concentrations, critical point drying, mounting, coating, and observation by scanning electron microscopy (SEM) are described. Cell suspensions of peripheral blood mononuclear cells, yeast (Saccharomyces cerevisiae), and actinomycete were prepared. Each sample was layered on PLL-coated cover glasses, incubated under physiological conditions, washed with phosphate buffer, and fixed with glutaraldehyde. The observation was performed using an Inspect™ (FEI) SEM. This method allowed the acquisition of high-quality images, which showed the ultrastructure of the three types of samples evaluated here and could be applied to other samples with similar characteristics.